2020
DOI: 10.3389/fgene.2020.00660
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Detection of HPV Integration Sites in Cervical Cancer Samples Using the Nanopore MinION Sequencer Without Error Correction

Abstract: During the carcinogenesis of cervical cancer, the DNA of human papillomavirus (HPV) is frequently integrated into the human genome, which might be a biomarker for the early diagnosis of cervical cancer. Although the detection sensitivity of virus infection status increased significantly through the Illumina sequencing platform, there were still disadvantages remain for further improvement, including the detection accuracy and the complex integrated genome structure identification, etc. Nanopore sequencing has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…However, it requires large amounts of sequencing data, and thus is not applicable in clinical usage, which requires fast and accurate results. To date, the development of new NGS methods for HPV integration detection with high accuracy and prompt reporting capacity is ongoing [ 52 ]. However, the best way currently to detect integration sites is reached by using probe-captured sequencing methods (see section “Enrichment protocols” below).…”
Section: Methodsmentioning
confidence: 99%
“…However, it requires large amounts of sequencing data, and thus is not applicable in clinical usage, which requires fast and accurate results. To date, the development of new NGS methods for HPV integration detection with high accuracy and prompt reporting capacity is ongoing [ 52 ]. However, the best way currently to detect integration sites is reached by using probe-captured sequencing methods (see section “Enrichment protocols” below).…”
Section: Methodsmentioning
confidence: 99%
“…Each DNA assay has its own limitations, for instance, DNA FISH is designed specifically for paraffin-embedded tissue, whereas quantitative PCR measures the relative E2 gene loss compared to E6, which may miss integration events that occur outside the E2 gene region. Nowadays, more studies focus on distinct DNA-seq techniques to capture HPV integration events, having shown to be more accurate and comprehensive [ 51 , 52 ]. However, whereas RNAseq methods may miss integration events that are transcribed but do not result in any viral-host fusion transcripts, the DNA approaches by their very nature cannot determine which integration events are transcribed.…”
Section: Dominant Role Of Hpv Integration In Defining Hpv(+) Tumor Characteristics and Subtypesmentioning
confidence: 99%
“…HPV is frequently integrated into the human genome [ 17 ]. The integration of high-risk human papillomavirus (HR-HPV) into the host genome is seen in ~85% of cervical squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…These facts suggest that recurrent loci provide clonal selection advantages that contribute to carcinogenesis. The target host genes observed in these “hot-spots” are enriched in genes that are continuously expressed during transcription and DNA repair [ 14 , 17 , 18 ]. Several integrations sites are located inside the introns of tumor suppressor genes (like SCAI and NR3C2 ), likely altering the original expression patterns and contributing to the complete loss of gene function [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation